Statins Decrease Oxidative Stress and ICD Therapies - Heather L. Bloom; Irfan Shukrullah; Emir Veledar; Rebecca Gutmann; Barry London; Samuel C. Dudley (Cardiology Research and Practice)
Recent studies demonstrate that statins decrease ventricular arrhythmias in internal cardioverter defibrillator (ICD) patients. The mechanism is unknown, but evidence links increased inflammatory and oxidative states with increased arrhythmias. We hypothesized that statin use decreases oxidation. Methods. 304 subjects with ICDs were surveyed for ventricular arrhythmia. Blood was analyzed for derivatives of reactive oxygen species (DROMs) and interleukin-6 (IL-6). Results. Subjects included 252 (83%) men, 58% on statins, 20% had ventricular arrhythmias. Average age was 63 years and ejection fraction (EF) 20%. ICD implant duration was 29 ± 27 months. Use of statins correlated with lower ICD events (r=0.12, P=.02). Subjects on statins had lower hsCRP (5.2 versus 6.3; P=.05) and DROM levels (373 versus 397; P=.03). Other factors, including IL-6 and EF did not differ between statin and nonstatin use, nor did beta-blocker or antiarrhythmic use. Multivariate cross-correlation analysis demonstrated that DROMs, statins, IL-6 and EF were strongly associated with ICD events. Multivariate regression shows DROMs to be the dominant predictor. Conclusion. ICD event rate correlates with DROMs, a measure of lipid peroxides. Use of statins is associated with reduced DROMs and fewer ICD events, suggesting that statins exert their effect through reducing oxidation.